Establishment of cephalometric norms using tetragon analysis in bengali population - Darshana Sarkar; Subhas Seth; Divya Jyoti; Mehedi Hasan; Adwitiya Pattanayak; Moitri Ojha (Journal of Pharmacy and Bioallied Sciences, 2023)
Introduction: The traits of craniofacial skeleton varies with race, ethnicity, and culture. Tetragon cephalometric analysis, first given by J Fastlight, et al. in 2000, consist of simple and efficient method of measuring the maxillomandibular relationship and their relation with cranial base. Aims of the Study: urpose of study is to establish cephalometric norms for tetragon analysis in the Bengali population and differences between Bengali males and females. Materials and Methods: A sample of 100 cephalometric radiographs of class I non-orthodontic subjects aged between 18 and 25 years were traced manually and parameters were statistically analyzed by independent t-test using SPSS software. Results: When compared to Fastlicht's Caucasian norms, the upper and lower jaws of the Bengali people are more prognathic and their incisors are relatively proclined. Both jaws were convergent in Bengali population (horizontal growth pattern). Bengali females had a more protrusive upper jaw, proclined anterior teeth, and vertical growth pattern when compared to Bengali males. Conclusion: Tetragon analysis is an efficient tool to quickly assess the dentoalveolar and jaw relations to formulate treatment goals and to compare treatment outcomes.